Characteristics of Various Moulds that Potentially as Decomposers Pineapple Industry By-Product - Sumardi, Sumardi; Dermiyati, Dermiyati; Yusnaini, Sri; Irawan, Bambang; Ramadani, Winih Sekaringtyas; Triyono, Sugeng (Jurnal Agroekoteknologi Tropika Lembab, 2025)
The purpose of this study was to determine the potency of three mold isolates Bio GGP2, Bio GGP3 and Bio GGP5. The mold isolate was isolated from pineapple waste. Molds are selected have cellulolytic, xylanolytic, ligninolytic, amylolytic, annanolytic, and proteolytic. Enzyme detection on agar media with suitable substrate. Then, the selected fungi were tested for their decomposition ability in pineapple waste. The results of the decomposition test showed that the combination of the three isolates gave the best results of 45% decomposed material at 14 days of age. The three isolates have the potential to be used to decompose cellulose waste from pineapple